Polymeric nanocarriers for cancer theranostics. (17th May 2017) - Vijayan, Vineeth M.; Muthu, Jayabalalan
Abstract : Theranostics is an emerging area in nanomedicine where therapeutic and diagnostic platforms are integrated together to perform multiple functions such as disease diagnostic and therapy, noninvasive method to determine the targeted delivery of drugs, and evaluation of drug efficacy. This review gives an overview of the different therapeutic and diagnostic strategies used to construct a theranostic system. The importance of polymer‐based theranostic carriers is presented. The different types of polymeric carriers such as micelles, liposomes, dendrimers, and nanogels explored for theranostic applications are also presented. Copyright © 2017 John Wiley & Sons, Ltd.